2007
DOI: 10.1093/eurheartj/ehm465
|View full text |Cite
|
Sign up to set email alerts
|

Growth-differentiation factor-15 improves risk stratification in ST-segment elevation myocardial infarction

Abstract: GDF-15 is a new biomarker in STEMI that provides prognostic information beyond established clinical and biochemical markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
154
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(171 citation statements)
references
References 27 publications
9
154
1
7
Order By: Relevance
“…Increased levels of GDF15/MIC-1 have been reported in several studies related to CVD or CV events, particularly in women 27,40,41 . A number of SNP have been analyzed for the GDF15/MIC-1 gene, and in particular SNP associated with promoter activity were associated with GDF15 protein level.…”
Section: Rheumatologymentioning
confidence: 87%
“…Increased levels of GDF15/MIC-1 have been reported in several studies related to CVD or CV events, particularly in women 27,40,41 . A number of SNP have been analyzed for the GDF15/MIC-1 gene, and in particular SNP associated with promoter activity were associated with GDF15 protein level.…”
Section: Rheumatologymentioning
confidence: 87%
“…[9][10][11][12][13][14][15][16] In clinically stable patients with acute decompensated heart failure, high levels of B-type natriuretic peptide (BNP) at the end of a hospitalization are strong, independent markers of CV events compared with levels during the acute phase.…”
Section: )mentioning
confidence: 99%
“…8) High-sensitivity C reactive protein (hs-CRP); growth differentiation factor-15 (GDF-15), a member of the transforming growth factor-β superfamily; and ST2, a member of the interleukin-1 receptor family, are strongly associated with CV events in AMI patients. [9][10][11][12][13][14][15][16] In clinically stable patients with acute decompensated heart failure, high levels of B-type natriuretic peptide (BNP) at the end of a hospitalization are strong, independent markers of CV events compared with levels during the acute phase. 17) Secondary prevention of CV events is a crucial factor for the prognostic improvement in patients with AMI, and novel biomarkers provide important information about patient management if the biomarkers contribute to the risk stratification in these patients.…”
mentioning
confidence: 99%
“…158 In prospective trials of ACS [the Global Utilization of Strategies To Open occluded arteries (GUSTO)-IV non-ST-elevation acute coronary syndrome trial 159 and the PRavastatin OR atorVastatin Evaluation and Infection Therapy -Thrombolysis In Myocardial Infarction 22 (PROVE IT-TIMI 22) trial 160 ] GDF15 has been shown to be a prognostic marker. GDF15 has been shown to be a long-term prognostic marker in patients admitted with NSTEMI 161 and a prognostic marker in STEMI 162,163 and in the general AMI population. 164 Measurement of GDF15 has been shown to be prognostic in the chest pain population 165 and to add to conventional risk scores such as the Global Registry of Acute Coronary Events (GRACE) score.…”
Section: Growth Differentiation Factor 15mentioning
confidence: 99%